The OPTION trial: outpatient induction of labour – study protocol for a prospective, non-inferiority, multicentre randomised controlled trial - Kristina Gemzell-Danielsson; Susanne Hesselman; Sophia Brismar Wendel; Magnus Domellöf; Ulla-Britt Wennerholm; Maria Jonsson; Verena Sengpiel; Helen Elden; Ylva Carlsson; Sofie Graner; Tove Wallström; Helena Kopp-Kallner; et al. (BMJ Open)
Introduction Sweden, as many other high-income countries, has adopted guidelines to offer induction of labour at 41+0 gestational weeks to decrease the risk for perinatal death. As more than 20% of the pregnant population reach this gestational age, and along with other contributing factors, induction rates have increased up to 30% in many countries. Both women and care providers have raised the question if outpatient induction could be a convenient, safe and economic alternative, reducing the burden on inpatient care in maternity hospitals. Before introducing outpatient induction into clinical routine, studies need to assure safety for the child and woman as well as efficacy of the method.Method and analysis A register-based randomised controlled multicentre non-inferiority trial to study if outpatient induction in low-risk inductions is (1) as safe for the child (perinatal composite of mortality and morbidity) and (2) as effective (proportion of vaginal deliveries) as inpatient induction at the hospital. Secondary outcomes are further health outcomes, experiences of pregnant women, partners and care providers, health economics and future pregnancy outcome. Participating women with a singleton pregnancy and unripe cervix between 37+0 and 41+6 gestational weeks planned for low-risk induction will undergo induction of labour with either a balloon catheter or oral misoprostol according to clinical practice at the study site and the woman’s informed choice. Randomisation will allocate women to either outpatient (home or patient hotel) or inpatient induction (standard care). Women undergoing outpatient induction can remain at home for up to 2 days, with an assessment after 24 hours including cardiotocography. Once active labour ensues, all women will receive standard care in the hospital.The assessment of non-inferiority will involve a two-sided 95% CI and 80% power, requiring randomisation of 8891 women to ensure a probability of at least 0.80 that the upper limit of a two-sided 95.7% CI for a difference in the primary safety outcome is below the non-inferiority margin of 1.5%. 31 of the 45 delivery units in Sweden are currently recruiting. Data will be collected from the electronic case report form and Swedish healthcare registers. Questionnaire and qualitative interview-based studies will be performed to explore experiences of pregnant women, partners and care providers. Additionally, a health economic evaluation will be performed.Ethics and dissemination The Swedish Ethical Review Authority approved the study (3 June 2020; 2020-02675 with amendments 2021-03045, 2022-00865-02, 2023-01252-02, 2024-00560-02, 2024-2024-04597-02). The Swedish Medical Products Agency approved the study for the medication arm (25 August 2020, EudraCT number: 2020-000233-41; 5.1-2020-60240 with amendments 5.1-2022-73500, 5.1-2023-630). Due to changed regulation, in 2023, the study medication arm was transferred and approved by the European Medicines Agency (23 October 2023, EU CT Number: 2023-507164-39-00; CTIS 5.1.2-2023-099775 with amendments 5.1.2-2024-081916, 5.1.2-2025-036291). The Swedish Medical Products Agency approved the study for the medical device arm (6 April 2021, CIV-ID: CIV-20-09-034712; 5.1-2021-14812 with amendments 5.1-2022-14252, 5.1-2023-596, 5.1-2024-8886, 5.1-2024-55554). The medical device arm was transferred to Regulation (EU) 2017/745 (23 December 2024, 5.1-2025-24242 and amendment 5.1-2025-6050). The study will involve more than 80% of all delivery units in Sweden, which will allow for a smooth implementation of any new routine after the study’s conclusion. Results will be published in relevant scientific journals, presented at national and international conferences, and communicated to participants and relevant institutions through the Outpatient Induction study homepage (www.optionstudien.se), the webinars of the Swedish Network for National Clinical Studies in Obstetrics and Gynecology (www.snaks.se) as well as social and public media.Trial registration number EudraCT No: 2020-000233-41, after transfer to the European Medicines Agency EU CT Number: 2023-507164-39-00; CIV-ID 20-09-034712.